2022
DOI: 10.3390/healthcare11010094
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Living Conditions and Psychological Distress in Japanese University Freshmen during the COVID-19 Pandemic

Abstract: Since the novel coronavirus disease 2019 (COVID-19) pandemic, educational institutions have implemented measures such as school closures, raising concerns regarding the increase in psychological distress among university students. The purpose of this study is to identify factors that have influenced psychological distress among college freshmen during the COVID-19 pandemic. A questionnaire survey was conducted at the conclusion of the sixth wave of COVID-19 in Japan. Psychological distress was measured using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Although our study was a cross-sectional survey conducted before and after the COVID-19 pandemic, the results of longer sleep duration after the COVID-19 pandemic were comparable to those reported by Hori et al Although the questionnaires used to evaluate psychological distress were different, the percentage of students suffering from psychological stress was higher (27.4%) in the study reported by Iio et al than that in the present study (11.4%). Because the years of data correction were 2022 [ 22 ] and 2020 (the present study), the continuation of behavioral restrictions due to the COVID-19 pandemic resulted in a higher percentage of students with psychological stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our study was a cross-sectional survey conducted before and after the COVID-19 pandemic, the results of longer sleep duration after the COVID-19 pandemic were comparable to those reported by Hori et al Although the questionnaires used to evaluate psychological distress were different, the percentage of students suffering from psychological stress was higher (27.4%) in the study reported by Iio et al than that in the present study (11.4%). Because the years of data correction were 2022 [ 22 ] and 2020 (the present study), the continuation of behavioral restrictions due to the COVID-19 pandemic resulted in a higher percentage of students with psychological stress.…”
Section: Discussionmentioning
confidence: 99%
“…Another study that evaluated sleep problems by examining digital media use suggested that students whose screen time increased during 2019 and 2020 were at higher risk for sleep problems [ 21 ]. Finally, Iio et al [ 22 ] surveyed Japanese first-year university students in mid-April 2022 and found that 27.4% of the participants experienced psychological distress due to sleep deprivation. Although our study was a cross-sectional survey conducted before and after the COVID-19 pandemic, the results of longer sleep duration after the COVID-19 pandemic were comparable to those reported by Hori et al Although the questionnaires used to evaluate psychological distress were different, the percentage of students suffering from psychological stress was higher (27.4%) in the study reported by Iio et al than that in the present study (11.4%).…”
Section: Discussionmentioning
confidence: 99%
“…The participants were then divided into two groups: those with high scores (poor mental health conditions: ≥ 5 points) and those with low scores (good mental health conditions: ≤ 4 points). Similarly, several previous studies have used a cut-off value of 5 points for this scale (16,22,23).…”
Section: Measurementsmentioning
confidence: 99%